Exploring academics' views on designs, methods, characteristics and outcomes of inclusive health research with people with intellectual disabilities: a modified Delphi study. Issue 8 (18th August 2016) - Frankena, T K; Naaldenberg, J; Cardol, M; Meijering, J V; Leusink, G; van Schrojenstein Lantman-de Valk, H M J
Abstract : Background: The British Medical Journal 's ( BMJ 's) patient revolution strives for collaboration with patients in healthcare and health research. This paper studies collaboration with people with intellectual disabilities (ID) in health research, also known as inclusive health research. Currently, transparency and agreement among academics is lacking regarding its main aspects, preventing upscaling of the patient revolution. Objective: This study aims to gain agreement among academics on 3 aspects of inclusive health research for people with ID: (1) designs and methods, (2) most important characteristics and (3) outcomes. Design: A Delphi study was conducted with academics with experience in inclusive (health) research and on people with ID. The study consisted of 2 sequential questionnaire rounds (n=24; n=17), followed by in-depth interviews (n=10). Results: Academics agreed on (1) a collaborative approach to be most suitable to inclusive health research, (2) characteristics regarding the accessibility and facilitation of inclusive health research, and (3) several outcomes of inclusive health research for people with ID and healthcare. Other characteristics agreed on included: atmosphere, relationship, engagement, partnership and power. It was stressed that these characteristics ensure meaningful inclusion. Interviewed academics voiced the need for a tool supporting the facilitation and evaluation of inclusive health research. There was ambiguity as to what this tool should comprise and the extent to which it was possible to capture the complex process of inclusive health research. Discussion and conclusions: This study underlines the need for transparency, facilitation and evaluation of inclusive health research. The need for in-depth interviews after 2 Delphi rounds underlines its complexity and context dependence. To increase process transparency, future research should focus on gaining insight into inclusive health research in its context. A tool could be developed to facilitate and evaluate inclusive health research. This tool will be partially applicable to participatory research in general and thereby upscale the patient revolution.